Local Civilizations in Eurasia: Long Term Scenario of Interaction - Alexey I. Podberezkin; Maxim V. Kharkevich (Vestnik MGIMO-Universiteta, 2015)
The article is devoted to analyzing the interactions of local civilization in the world and in Eurasia. The authors pays close attention to the theoretical issues of the subject matter. They choose for their analysis the nonessential conception of civilization. It allows societies with in a single civilization with radically different views on the civilizational reference framework. This conception explains why there are more clashes within a civilization, then among them. Then the author dwell sont he issue of civilizational conflict in Eurasia. The focal point of the conflict is the clash between Russian and American local civilizations. The authors develop the most probable scenario of civilizational interaction, which is their arm conflict. Then they develop three variations of this scenario: optimistic, realistic and pessimistic. The authors believ et hatby2020 Western local civilization will lose its political monopoly. It means that Russia should be ready with successes with its integration projects in Eurasia. Other wise it can fall preyto China.